Doubting Ghosts: Paranormal Investigations and the Paradoxes of Belief, by Michele Hanks - Parker, Jacques (International journal for the study of new religions, 2023)
Doubting Ghosts: Paranormal Investigations and the Paradoxes of Belief, by Michele Hanks. London and New York: Routledge, 2025. Pb. viii + 193 pp. $43.99. ISBN: 9781032655789